Hands-on cybersecurity with Blockchain implement DDoS protection, PKI-based identity, 2FA, and DNS security using Blockchain - Gupta, Rajneesh (Packt Publishing, 2018)
Despite the growing investment in cybersecurity, modern attackers manage to bypass advanced security systems. Blockchain and Hyperledger architecture provide a safer way of avoiding such attacks. This book will help you build blockchain-based apps for DDoS protection, PKI-based identity platform, Two-factor authentication and DNS Security platform.